SPATIAL AND TEMPORAL VARIABILITY OF OCEANOGRAPHIC PARAMETERS OF FISH CAPTURED IN THE SEA OF BENGKULU (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Sea territorial of Bengkulu has abundantly fish resource which influenced by oceanographic parameters. The purpose of this research is to determine the variability of spatially and temporally oceanographic parameters and their relationships to the fish catch in Bengkulu seas for 5 years. The method used is descriptive analysis based on the data of visualization of wind speed, sea surface temperature, and salinity in the periods of 2011-2015. The data were analyzed by using GrADS software. The results show the highest of fish catch occurred on the west season of 2015 with 16.514 tons. The wind speed at that season was1.211 m/s, Sea Surface Temperature (SST) of 29.094 oC, and salinity of 33.62 psu. Mean while, the lowest fish catch on the west season of 2012 with 7,576.60 tons. The wind speed at that season was 4.624m/s, SST of 28.765 oC, and salinity of 33.987 psu. The relationship between oceanographic condition and the fish catch is generally described, i.e., when high of sea wind speed and salinity, and low sea surface temperature will be obtained low fish catch. On the contrary, when low wind speed and salinity, and high sea surface temperature will be obtained high fish catch.